2018
DOI: 10.1038/nature26164
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: The Beaker phenomenon and the genomic transformation of northwest Europe

Abstract: This corrects the article DOI: 10.1038/nature25738.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…When studying the demographic history of humans, aDNA has been shown to be an irreplaceable source of information. aDNA studies have revealed large-scale population movements and genetic turnover events in Western Eurasia [17][18][19][20] that were otherwise impossible to recover from human genetic data of modern-day populations. Studies of the uniparentally inherited markers of ancient individuals have also yielded otherwise undetectable results, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When studying the demographic history of humans, aDNA has been shown to be an irreplaceable source of information. aDNA studies have revealed large-scale population movements and genetic turnover events in Western Eurasia [17][18][19][20] that were otherwise impossible to recover from human genetic data of modern-day populations. Studies of the uniparentally inherited markers of ancient individuals have also yielded otherwise undetectable results, e.g.…”
mentioning
confidence: 99%
“…Studies of the uniparentally inherited markers of ancient individuals have also yielded otherwise undetectable results, e.g. the loss of European mtDNA diversity following the repeopling of Europe after the last glacial maximum 10 , or the decrease in and partial replacement of diversity of hunter-gatherer Y-chromosome lineages in eastern and central Europe following the Neolithic expansion [21][22][23][24] , followed by the loss of diversity of Neolithic Y-chromosomes lineages with the arrival of Steppe-like ancestry at the beginning of the 3 rd millennium BCE 15,[18][19][20] .…”
mentioning
confidence: 99%
“…18 reported a HV haplotype in one sample from Serbia dating from 5800 BCE. Moreover, haplogroup HV was observed in Copper Age specimens from Scotland, Hungary and Germany 25 and in Hungarian and Israeli samples from the Chalcolithic period 26,27
Figure 2Median Joining Network representing the phylogenetic relationships between the new Thracian samples (highlighted in red labels) and the ancient reference dataset. Major mitochondrial lineages and sub-lineages are indicated by different colors as specified in the legend at the top-left.
…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays the highest observed European frequency of the lineage K is in Bulgaria (13.3%) 28 and K1c is particularly common in Slavic-speaking countries. In ancient populations, the haplogroup K1c has been identified in six hunter-gatherers dated before the arrival of farming (one in Romania, three in Serbia 18 and two in Greece 29 ), in two Bronze-Age individuals from Hungary and Bulgaria 18,30,31 and in two Central-Europe farmers associated with the Bell-Beaker culture 25,32,33 . The phylogenetic network analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess links between diet and cultural evolution on the GHP, stable isotope and ancient DNA (aDNA) research has been conducted on samples from the Neolithic through Iron Age 42 , 58 61 . Previous carbon and nitrogen stable isotope analyses of human and faunal osteological samples from this region have focused primarily on Neolithic and Copper Age populations, reporting a transformation in subsistence strategies during the Late Neolithic and Copper Age towards increased consumption of animal protein compared to the previous subperiods 58 , 62 – 65 .…”
Section: Introductionmentioning
confidence: 99%